Cracking seeds and nuts: Replicating use-wear on pitted ground-edged stone hatchets from Southeastern Australia. (June 2021) - Kononenko, Nina; Attenbrow, Val; White, Peter; Asmussen, Brit; Torrence, Robin
Highlights: Experimental seed and nut cracking produced diagnostic use-wear on hammers and anvils. Distinguishable use-wear is only produced after several hours of percussive activity. Southeast Australian ground stone hatchet heads were used for plant processing. Abstract: The presence of small depressions on stone tools found in various parts of Australia has frequently been assumed to be the consequence of bipolar knapping. In contrast, Pardoe et al. (2019) and Attenbrow and Kononenko (2019) proposed that these attributes derive from their use for nut cracking. To test this hypothesis, we conducted experiments using the hammer and anvil technique to crack Macrozamia seeds and macadamia nuts for prolonged periods. The use-wear traces that developed on the experimental tools were found to compare favourably with those on a sample of 11 ground-edged hatchets from the Central Coast, New South Wales. Our results suggest that the consumption of seeds and nuts in pre-contact Aboriginal diets in south eastern Australia might have been more significant than currently recognised and should be investigated further.